2019
DOI: 10.1021/acs.jpca.8b12240
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Chemistry of Enols: Vinyl Alcohol + OH + O2Reaction Revisited

Abstract: The OH-initiated oxidation of vinyl alcohol (VA) produced by phototautomerization of acetaldehyde is thought to be a source of formic acid (FA) in the atmosphere. A recent theoretical study predicted that the VA + OH + O 2 reaction 1 proceeds by OH addition at α-C (66%) and β-C (33%) of VA and that FA is a main product of reaction 1. However, the metastable reactant (anti-VA, ∼18% at 298 K, 1.42 kcal mol −1 higher than syn in energy) used in that study inspired us to reinvestigate reaction 1. Using the state-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
39
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 61 publications
8
39
1
2
Order By: Relevance
“…Furthermore, the work of Lim et al has shown aqueous chemistry in SOA formation including aldol condensation, sulfur esters formation, and oligomerization of hydrated glyoxal enols . Another theoretical study by Lei et al showed atmospherically relevant reactions of ethenol with OH radical, with glycolaldehyde is predicted to be the main product . According to these observations, our results strongly suggest that it may be possible that MA in the atmospheric OA particles can undergo unpredicted chemical reactions with other organic compounds and form low-volatility SOA products in the presence of highly reactive species such as OH radical.…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, the work of Lim et al has shown aqueous chemistry in SOA formation including aldol condensation, sulfur esters formation, and oligomerization of hydrated glyoxal enols . Another theoretical study by Lei et al showed atmospherically relevant reactions of ethenol with OH radical, with glycolaldehyde is predicted to be the main product . According to these observations, our results strongly suggest that it may be possible that MA in the atmospheric OA particles can undergo unpredicted chemical reactions with other organic compounds and form low-volatility SOA products in the presence of highly reactive species such as OH radical.…”
Section: Discussionsupporting
confidence: 64%
“…[37] Recently, Coggins and Powner [38] demonstrated the synthesis of phosphoenol pyruvate (7), a high energy phosphate found in living organisms, from prebiotic precursors such as glycolaldehyde and glyceraldehyde. Enols have been suggested as important reactive intermediates for the formation of secondary organic aerosols in the atmosphere, [39][40][41][42][43] as enols can readily be oxidized to carboxylic acids in the gas phase. [41,43,44] The fragmentation of molecular precursors presents a suitable entry point to explore the synthesis of enols in the gas phase.…”
mentioning
confidence: 99%
“…Enols have been suggested as important reactive intermediates for the formation of secondary organic aerosols in the atmosphere, [39][40][41][42][43] as enols can readily be oxidized to carboxylic acids in the gas phase. [41,43,44] The fragmentation of molecular precursors presents a suitable entry point to explore the synthesis of enols in the gas phase. As established historically, dicarboxylic acids are attractive enol precursors due to their facile preparation, their tendency to undergo thermal decarboxylation under mild conditions, and their release of an inert and neutral byproduct (Scheme 1).…”
mentioning
confidence: 99%
“…[37] Erst kürzlich legten Coggins und Powner [38] die Synthese des hochenergetischen Phosphats Phosphoenol-Pyruvat (7), das bereits in lebenden Organismen nachgewiesen wurde, aus präbiotischen Vorläuferverbindungen wie Glykolaldehyd und Glyceraldehyd dar. Enole werden ebenfalls als wichtige reaktive Intermediate für die Bildung sekundärer, organischer Aerosole in der Atmosphäre in Betracht gezogen, [39][40][41][42][43] da sie in der Gasphase leicht zu Carbonsäuren oxidiert werden kçnnen. [41,43,44] Die Fragmentierung molekularer Vorläuferverbindungen stellt eine passable Strategie für die Darstellung von Enolen in der Gasphase dar.…”
unclassified
“…Enole werden ebenfalls als wichtige reaktive Intermediate für die Bildung sekundärer, organischer Aerosole in der Atmosphäre in Betracht gezogen, [39][40][41][42][43] da sie in der Gasphase leicht zu Carbonsäuren oxidiert werden kçnnen. [41,43,44] Die Fragmentierung molekularer Vorläuferverbindungen stellt eine passable Strategie für die Darstellung von Enolen in der Gasphase dar. Wie historisch bereits belegt, eignen sich Dicarbonsäuren durch ihre einfache Darstellung, ihr Bestreben unter milden Bedingungen zu Decarboxylieren und die damit verbundene Freisetzung eines neutralen Nebenprodukts ideal als Enolvorläuferverbindungen (Schema 1).…”
unclassified